Involvement of serotonergic system in the effect of a metabotropic glutamate 5 receptor antagonist in the novelty-suppressed feeding test - Kenichi Fukumoto; Shigeyuki Chaki (Elsevier, 2015)
The blockade of metabotropic glutamate 5 (mGlu5) receptor has been reported to exert antidepressant effects in several animal models. We previously reported that both ketamine and an mGlu5 receptor antagonist exerted an effect in a novelty-suppressed feeding (NSF) test, and that the effect of ketamine may be mediated through an α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptor-dependent increase in serotonergic transmission. However, the involvement of the serotonergic system in the effect of mGlu5 receptor antagonists in the NSF test is not well understood. Therefore, we examined the roles of the serotonergic system in the effect of an mGlu5 receptor antagonist, 6-methyl-2-(phenylethynyl)pyridine hydrochloride (MPEP), in the NSF test in mice. The administration of MPEP significantly shortened the latency to feed, which was not attenuated by the AMPA receptor antagonist, 2,3-dioxo-6-nitro-1,2,3,4-tetrahydrobenzo[f]quinoxaline-7-sulfonamide (NBQX). The effect of MPEP was abolished by the tryptophan hydroxylase inhibitor, para-chlorophenylalanine (PCPA). Moreover, the effect of MPEP was blocked by a serotonin (5-HT)2A/2C receptor antagonist, ritanserin, but not by a 5-HT1A receptor antagonist, N-{2-[4-(2-methoxyphenyl)-1-piperazinyl]ethyl}-N-(2-pyridynyl) cyclohexane-carboxamide (WAY100635). These results suggest that the effect of an mGlu5 receptor antagonist may be mediated by the serotonergic system, including the stimulation of the 5-HT2A/2C receptor, in an AMPA receptor-independent manner in the NSF test.